Evaluation of the macrofauna of the soil associated to different systems with cofee Coffea arábiga L. - Delgado, Gilma; Burbano, Aracely; Silva Parra, Amanda (Revista de Ciencias Agrícolas, 2011)
The study was carried in municipality of San Pedro De Cartago, Department of Nariño, located 1 ° 35’21’’N and 77 ° 08’38"W. It investigation about a macrofauna of soil associated with different ways of production of Coffea arabiga: C. arabiga and Musa sapientum, C. arabiga and Inga edulis L. and C. arabiga and the forest. The sample did methodology the Tropical Soil Biology and Fertility Program (TSBF) Oliveira, 2000. The higher abundance of macrofauna was found in the forest uses and C. arabiga associated with M. sapientum, then the associated system of C. arabiga with Inga edulis, the lowest percentages in the monocultivo C. arabiga. The results indicated that the forest and the system agroforestal C. arábiga and I. edulis they presented a main diversity and biomass, to difference of the system C. arabiga in monocultivo which determined the lowest level. The C. arabiga was different, because it found the lowest level. Respect to the vertical distribution most productivity and diversity in the level 0 to 10 cm, with 15 families that made 4496 i.p.m2, and a diversity chagod of 0,52 the system C. arabiga and I. edulis and 0,32 for C. arabiga in according to Simpson.